2020
DOI: 10.1111/bph.14965
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the gut microbiota induced by losartan contributes to its antihypertensive effects

Abstract: Background and Purpose: Hypertension is associated with gut dysbiosis. Here we have evaluated the effects of the angiotensin receptor antagonist losartan on gut microbiota in spontaneously hypertensive rats (SHR) to assess their contribution to its antihypertensive effects.Experimental Approach: Twenty-week-old Wistar Kyoto rats (WKY) and SHR were treated with losartan for 5 weeks (SHR-losartan). Faecal microbiota transplantation (FMT) was performed from donor SHR-losartan group to recipient untreated-SHR.Bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 67 publications
2
79
0
3
Order By: Relevance
“…This is the case of patients with anti-hypertensive treatment, which included in many cases a complex of different angiotensin II receptor blockers, angiotensin-converting enzyme inhibitors, diuretics, calcium channel blockers, and β-1 adrenergic blockers. Although there are no human studies that specifically address the possible effect of this mixture of anti-hypertensive drugs on the gut microbiota [48], a recent study shows that the angiotensin receptor blocker losartan exerted anti-hypertensive effects, at least partially, by modulating the gut microbiota of spontaneously hypertensive rats [49]. Nevertheless, we speculate that the significant structural variability of anti-hypertensive drugs might prevent the elucidation of common mechanisms of action (either direct or indirect) on the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of patients with anti-hypertensive treatment, which included in many cases a complex of different angiotensin II receptor blockers, angiotensin-converting enzyme inhibitors, diuretics, calcium channel blockers, and β-1 adrenergic blockers. Although there are no human studies that specifically address the possible effect of this mixture of anti-hypertensive drugs on the gut microbiota [48], a recent study shows that the angiotensin receptor blocker losartan exerted anti-hypertensive effects, at least partially, by modulating the gut microbiota of spontaneously hypertensive rats [49]. Nevertheless, we speculate that the significant structural variability of anti-hypertensive drugs might prevent the elucidation of common mechanisms of action (either direct or indirect) on the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In general, they demonstrate significant dysbiosis due to a reduction in microbial richness, diversity, evenness, and a rise in the Firmicutes/Bacteroidetes (F/B) ratio in renin-dependent hypertension in both animal model, such as spontaneously hypertensive rats (SHR), and essential hypertensive patients. 1,3,4,7,8 Patients with low renin, particularly African Americans, represent a significant number of essential hypertensives and exhibit low efficacy for inhibitors of the renin-angiotensin pathway. African Americans with high blood pressure had a distinct gut microbiota taxonomy and showed marked differences in the function of the microbiota when compared with hypertensive White Americans.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an imbalance in the gut microbiota composition relative to the healthy state, termed dysbiosis, has been associated with hypertension [1][2][3][4]. The characteristics of dysbiosis are different between systemic renin-angiotensin system (RAS)-dependent hypertension, such as in spontaneous hypertensive rats (SHR) [1,3,[5][6][7], and systemic RAS-independent forms, such as hypertension induced by mineralocorticoid receptor activation [8,9]. Studies using fecal microbiota transplantation procedures have demonstrated that gut microbiota from hypertensive animals and human increased blood pressure (BP), showing a cause-effect relationship [3,10,11], albeit the mechanisms involved in BP regulation by the microbiota have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, inhibition of T cell activation and helper T (Th)17 differentiation reduced the hypertensive effect induced by dysbiotic microbiota from SHR, showing that immune system dysregulation induced by the gut microbiota may be, at least partially, responsible for the development of hypertension [3]. Interestingly, the improvement of gut dysbiosis induced by probiotic bacteria [7,9,14], dietary fiber [8], or by drug treatment [6,15], in several experimental models of hypertension, was involved in their antihypertensive effects. However, the antihypertensive drug hydralazine was unable to improve gut dysbiosis in SHR despite intensive BP reduction, showing that gut microbiota composition was not adapted to the host health status of normotension [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation